Development of CTIL Model Textbooks Based on H5P Application to Improve Students' Critical Thinking Skills - Hasyim, Faiz; Wibowo, Hari Anggit Cahyo; Wilujeng, Indrawati; Anwar, Mohammad Syaiful (Jurnal Ilmiah Pendidikan Fisika, 2024)
21st Century Skills are key competencies crucial for students to thrive and succeed in the future. Critical thinking skills are one of the urgent 21st-century skills. Students' critical thinking skills must be trained with the right learning models and textbooks. This study aims to develop a valid and practical H5P-based Critical Thinking-Independent Learning (CTIL) textbook to improve students' critical thinking skills. The research instruments were textbook validation sheets and textbook readability questionnaires. The data analysis used quantitative descriptive techniques. Quantitative descriptive analysis was carried out on the results of experts' validation and the textbook readability questionnaire. Based on the results of the research conducted, it was found that the validation result from the material expert was 3.81 in the very valid category, from the language expert was 3.80 in the very valid category, and from the media expert was 3.23 in the valid category. The results of the textbook readability questionnaire stated that the textbook was easy to understand, easy to use, and interesting, and students enjoyed using the H5P-based CTIL textbook with an average percentage of 82% in the very high category. Based on the results of the analysis, it can be concluded that the developed H5P-based CTIL textbook is valid and practical. Further research can be conducted by empirically testing the H5P-based CTIL textbook to determine its practicality in science learning broadly.